The problem of personnel consulting in Russia - Kremer M. I., Aldakusheva A. B. (Interactive science, 2017)
this article describes the problem concerning personnel consulting in Russia. According to the authors, personnel consulting is a relatively independent segment of the management consulting market.
Keywords: технология управления персоналом; кадровый консалтинг; HR-consulting; HR-консалтинг; управленческий консалтинг; В2В услуги; коррекция бизнес-модели; human resource consulting; HR consulting; management consulting; B2B services; human resource management technology; the correction of the business model